Phloretin Prevents Diabetic Cardiomyopathy by Dissociating Keap1/Nrf2 Complex and Inhibiting Oxidative Stress - Ying, Yin; Jin, Jiye; Ye, Li; Sun, Pingping; Wang, Hui; Wang, Xiaodong (Frontiers in Endocrinology, 2018)
Hyperglycemia induces chronic inflammation and oxidative stress in cardiomyocyte，which are the main pathological changes of diabetic cardiomyopathy (DCM). Treatment aimed at these processes may be beneficial in DCM. Phloretin (PHL), a promising natural product, has many pharmacological activities, such as anti-inflammatory, anticancer and anti-oxidative function. The aim of this study was to investigate whether PHL could ameliorate the high glucose-mediated oxidation, hypertrophy and fibrosis in H9c2 cells and attenuate the inflammation- and oxidation-mediated cardiac injury. In this study, PHL induced significantly inhibitory effect on the expression of pro-inflammatory, hypertrophy, pro-oxidant and fibrosis cytokines in high glucose-stimulated cardiac H9c2 cells. Furthermore, PHL decreased the levels of serum lactate dehydrogenase, aspartate aminotransferase and creatine kinase-MB, and attenuated the progress in the fibrosis, oxidative stress and pathological parameters via Kelch-like ECH-associated protein 1 (Keap1)/nuclear factor E2-related factor 2 (Nrf2) pathway in diabetic mice. In additional, molecular modeling and immunoblotting results confirmed that PHL might obstruct the interaction between Nrf2 and Keap1 through direct binding Keap1 and promoting Nrf2 expression. These results provided evidence that PHL could suppress high glucose-induced cardiomyocyte oxidative and fibrosis injury, and that targeting Keap1/Nrf2 may provide a novel therapeutic strategy for human DCM in the future.